The Effects of Autoclaving, Salt and Protein on Antimicrobial Activities of Iranian Sumac - Gh Amin; MM Ahmadian - Attari; MR Fazeli; H Jamalifar; H Ashtiani; A Ghobadi; R Shakiba; M Khanlarbeik (Institue of Medicinal Plants, ACECR, 2008)
Although many compounds have already approved for use in food as antimicrobials, research for finding greater number of these compounds are still interesting because most currently approved food antimicrobials have limited applications due to food compound interactions. Finding new food antimicrobials requires expensive investigations. Traditional herbal antimicrobial agents like sumac can play an important role. If it is demanded to promote sumac to the rank of a food antimicrobial agent, its stability and interactions must be evaluated. The evaluation of sumac heat stability was done by measuring MICs and MBCs of the extract against some food- related bacteria in extreme condition of autoclaving. The main components of sumac extract are tannic compounds. Tannins have interactions with salt and proteins, and they become sediment in such conditions. Antimicrobial activities of the extract were measured by well diffusion method in the presence of salt and protein and compared with the activities of pure extract. The results show that sumac is heat stable but has interactions with salt and proteins that reduce its activity against Gram- negatives.